A Novel VSC HVDC Frequency Control Strategy based on Neural Network Power Estimation using ROCOF. Issue 4 (2019) - Jeong, Soseul; Junghun, Lee; Jang, Gilsoo
Abstract: This paper introduces a novel VSC HVDC frequency control strategy by Active Power Estimation. Although VSC HVDC has a much faster control speed than synchronous generator, frequency control of VSC is similar to that of governor. If VSC can use the fast-control character in frequency control, frequency stability can be improved. For fast control, proper power order is important and to estimate the power, this paper uses a neural network that solves the nonlinear relationship between input and output easily. To make quick control before the frequency reaches nadir, ROCOF is used as an input variable of the neural network. It can be seen that when the load of the system is greatly changed, the frequency fluctuation is significantly lowered when the VSC changes the output by the estimated power. Control of the VSC through the neural network is expected to enable faster frequency control than previously possible.